A new Arthromacra W. Kirby, 1837 (Coleoptera: Tenebrionidae: Lagriinae) from the Great Himalayas - Telnov, Dmitry (Baltic Journal of Coleopterology, 2024)
Arthromacra annapurna sp. nov. from the Great Himalayas range in Nepal is described and illustrated. The new species is peculiar among the congeners in the non-metallic dorsum, the comparatively large body and the sparsely punctured elytra.